Search for lepton-flavour-violating decays of the Higgs and Z bosons with the ATLAS detector - Alconada Verzini, María Josefina (2017)
Direct searches for lepton flavour violation in decays of the Higgs and Z bosons with the ATLAS detector at the LHC are presented. The following three decays are considered: H → eτ , H → μτ, and Z → μτ. The searches are based on the data sample of proton–proton collisions collected by the ATLAS detector corresponding to an integrated luminosity of 20.3 fb−1 at a centre-of-mass energy of √s = 8 TeV. No significant excess is observed, and upper limits on the lepton-flavour-violating branching ratios are set at the 95% confidence level: Br(H → eτ) < 1.04%, Br(H → μτ) < 1.43%, and Br(Z → μτ) < 1.69 × 10−5.